ANALISIS KEBUTUHAN GURU DAN PESERTA DIDIK PADA PENGEMBANGAN E-BOOK TERINTEGRASI PROFIL PELAJAR PANCASILA - Maulidya, Rahmanita; Basri, Muhammad; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research uses a qualitative descriptive method with a case study approach to analyze the needs of teachers and students in making e-books integrated with the Pancasila student profile for Economics subjects at SMA Negeri 1 Pontianak. Teachers currently only use PowerPoint as learning media, but students face obstacles in understanding the material with this media. Generation Z students want learning media that is more interesting and relevant to the latest technology, such as animation, graphics, and video. They also want learning materials that are short, clear, and easy to understand. E-books integrated with the Pancasila learner profile can be the right solution with short, concise material and multimedia elements. Thus, this e-book has the potential to improve students' learning outcomes in learning Economics and help them understand Pancasila values more effectively. Teachers also need interesting learning media and face limited learning resources. By paying attention to these needs, this e-book can be an effective tool in improving Economics learning at SMA Negeri 1 Pontianak.